Beyond family‐level adversities: Exploring the developmental timing of neighborhood disadvantage effects on the brain. Issue 1 (4th June 2020) - Gard, Arianna M.; Maxwell, Andrea M.; Shaw, Daniel S.; Mitchell, Colter; Brooks‐Gunn, Jeanne; McLanahan, Sara S.; Forbes, Erika E.; Monk, Christopher S.; Hyde, Luke W.
Abstract: A growing literature suggests that adversity is associated with later altered brain function, particularly within the corticolimbic system that supports emotion processing and salience detection (e.g., amygdala, prefrontal cortex [PFC]). Although neighborhood socioeconomic disadvantage has been shown to predict maladaptive behavioral outcomes, particularly for boys, most of the research linking adversity to corticolimbic function has focused on family‐level adversities. Moreover, although animal models and studies of normative brain development suggest that there may be sensitive periods during which adversity exerts stronger effects on corticolimbic development, little prospective evidence exists in humans. Using two low‐income samples of boys ( n = 167; n = 77), Census‐derived neighborhood disadvantage during early childhood, but not adolescence, was uniquely associated with greater amygdala, but not PFC, reactivity to ambiguous neutral faces in adolescence and young adulthood. These associations remained after accounting for several family‐level adversities (e.g., low family income, harsh parenting), highlighting the independent and developmentally specific neural effects of the neighborhood context. Furthermore, in both samples, indicators measuring income and poverty status of neighbors were predictive of amygdala function, suggesting that neighborhood economic resources may be critical to brain development. Abstract : Across two prospective longitudinal studies, Census‐derived neighborhood disadvantage in early childhood was associated with greater amygdala reactivity to ambiguous facial expressions in adolescent and young adult men. These associations remained statistically‐significant after accounting for a host of family‐level adversities (i.e., low family income and maternal education, maternal depression, harsh parenting, inter‐parental conflict) during early childhood and neighborhood disadvantage during adolescence.